Analysis of the Sibaliparriq Concept from a Gender Equality Point of View; Examining the Views of Nahdatul Ulama and Muhammadiyah - Dermawan; Taudiyah, Nasya Tisyfa (Mazahibuna: Jurnal Perbandingan Mazhab, 2021)
This study entitled Gender Equality Analysis of the Sibaliparriq Concept in Polewali Mandar Regency (Study of the View of Nahdatul Ulama and Muhammadiyah) puts it into three problem formulations, among others are: How is the Sibaliparriq concept in Polewali Mandar? How do community leaders in Polewali Mandar view Sibaliparriq? And how are the views of Nahdatul Ulama and Muhammadiyah in Polewali Mandar towards Sibaliparriq in line with gender equality in Islam? In answering these problems, the author uses a sociological approach, which is a social approach that studies living together in society. This type of research is field qualitative or field research, which clearly describes the location and object to be studied, systematically, factually and accurately. The data sources used are primary data sources, namely parties or sources who have direct contact with Sibaliparriq's behavior, or sources obtained from informants through observation and interviews. While secondary data sources, namely data obtained in writing or research results about Sibaliparriq, as well as other sources that can add data to this research. The results of this study are about the Sibaliparriq culture adopted by the Mandar community, especially Patoke Village, Sulaluang Village, that the concept of Sibaliparriq which means helping each other, working together, between husband and wife in the household, for example the husband goes to the rice fields, the wife at home also takes busy selling, with this Sibaliparriq very helpful especially in improving the economy in the household, which has become the grip of the mandar community that there will be no problems in the household when there is awareness from a wife to help her husband, for the sake of creating harmony in the household. In addition, Sibaliparriq is certainly very in line with the teachings of Islam, there is no prohibition against a wife working to help her husband, departing from this understanding, it is explained in the Koran (QS al-Nahl 16:97) that Allah does not discriminate between men and women